What are ChatGPT and its Friends? : opportunities, costs, and risks for large language models - Loukides, Michael Kosta (O'Reilly Media, Inc., 2023)
ChatGPT is not your run-of-the-mill automated chat server. It's much more. But if you want to understand the possibilities that ChatGPT (and similar models) offers your organization, it's important to move past the hype. Large language models like GPT-3 and GPT-4 represent one of the biggest technological leaps we've seen in our lifetime. In this concise report, Mike Loukides zeros in on the essential things you should understand to take advantage of ChatGPT.